Quantitative proteomics - Aebersold, Ruedi (Henry Stewart Talks, 2008)
Proteomics, Quantitative mass spectrometry, Stable isotope labelling, Label free protein quantification, PeptideAtlas project, Targeted mass spectrometry via multiple reaction monitoring